1992
DOI: 10.1177/000348949210100503
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss as a Sequel of Lumbar Puncture

Abstract: Only a few case reports have been published about hearing impairment following lumbar puncture, and not all were thoroughly documented by audiograms. We present nine cases of hearing loss following myelography, lumbar puncture, and spinal anesthesia. We speculate that this rare complication arises only in persons with a wholly or partially patent cochlear aqueduct, and occurs via the release of perilymphatic fluid in the cerebrospinal space. Hearing loss was seen in eight of the nine patients in the lower freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 8 publications
1
59
0
3
Order By: Relevance
“…A similar application is during open or endovascular thoracoabdominal aortic artery aneurysm repair, for intraoperatively preventing or postoperatively treating spinal cord ischaemia [15]. A useful application of FRED, as we also showed, is in the diagnosis of NPH or the treatment of idiopathic intracranial hypertension, as serial lumbar taps are uncomfortable for the patient and hold a number of complications (cranial nerve VI and VIII palsies [16][17][18], spinal epidural CSF collection [19] and chronic tonsilar herniation-"acquired" Chiari malformation [20]). …”
Section: Constant Flow and Icpmentioning
confidence: 62%
“…A similar application is during open or endovascular thoracoabdominal aortic artery aneurysm repair, for intraoperatively preventing or postoperatively treating spinal cord ischaemia [15]. A useful application of FRED, as we also showed, is in the diagnosis of NPH or the treatment of idiopathic intracranial hypertension, as serial lumbar taps are uncomfortable for the patient and hold a number of complications (cranial nerve VI and VIII palsies [16][17][18], spinal epidural CSF collection [19] and chronic tonsilar herniation-"acquired" Chiari malformation [20]). …”
Section: Constant Flow and Icpmentioning
confidence: 62%
“…Increase in epidural pressure by epidural injection has been used to treat hearing loss [17]. Although there is no comparison of hearing loss with SSS and CSE with epidural volume extension, there is one trial, by Kilickan et al [16], comparing SSS with CSE without epidural volume extension.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle effects of CSF loss on hearing loss may be more common; a study of 34 patients administered spinal anesthesia found a consistently elevated hearing threshold at 500 Hz, with one patient demonstrating pronounced unilateral hearing loss that resolved after epidural blood patching [121]. Similarly, there exist several case reports of hearing loss after lumbar puncture or lumbar myelography with transient, low frequency hearing loss that was responsive to epidural blood patching [73,83,90,99].…”
Section: Acute Csf Lossmentioning
confidence: 99%
“…Hearing loss has been described following neurosurgery, lumbar puncture, myelography, and spinal anesthesia. Complete recovery of auditory function typically occurs within days of the procedure [73,83,90,99,123,124]. In contrast, chronic hearing loss has been described in patients with hydrocephalus [34,63,108] and other disorders of CSF pressure [32,52,81,92,94,104,105].…”
Section: Introductionmentioning
confidence: 99%